Deign of Broad Band Gap-Coupled Microstrip Antenna Using Microwave Office 7.5 (Al-Mansour Journal, 2022)
The objective of this paper is to design a compact and broadband microstrip patch antenna which operates at 2.9GHz center frequency with parasitically coupling rectangular microstrip antenna RMSA. Several parasiticallycoupled geometries are studied here.Thes are: radiating edge and non radiating edge gap-coupled RMSA with parasitic patches, one, two and four parasitic patches are being presented. The antenna has been analyzed using Microwave Office package software 7.5 in 2007. This proposed structure can have an operating bandwidth more than six times than that of the conventional rectangularpatch antenna